Strategi Pembangunan Masyarakat Desa Kebonagagung Pasca Gempa Bumi - Novitasari; Martinus Legowo; Katon Galih Setyawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to identify the community development strategy of Kebonagung Village after the earthquake. The research location is in Kebonagung Village, Wonodadi District, Blitar Regency. This research uses descriptive qualitative method. Sources of data used are primary and secondary data. Data collection techniques through observation, in-depth interviews, and documentation. The results showed that the condition of the people of Kebonagung Village after the earthquake was that some people had a sense of trauma and enthusiasm, lacked basic needs, and experienced losses. The community development strategy of Kebonagung Village after the earthquake was the community’s spirit, making good use of government assistance, praying and making efforts, and carrying out the rebowekasan tradition as a repellent against reinforcements. Obstacles to its implementation were found that some people have fear, mutual cooperation activities are not running well, economic losses, and some people do not carry out traditions. Meanwhile, the role of the Blitar Regency government in community development is to provide encouragement, socialization, assistance, and the establishment of disaster posts. In this case, it shows that the development strategy carried out by the people of Kebonagung Village is used a way to deal with the post-earthquake accompanied by assistance by the government so that life can return to normal and increase the capacity of the community in development based on disaster risk reduction.